Ibrutinib disrupts blood-tumor barrier integrity and prolongs survival in rodent glioma model - Sanghee Lim; Minhye Kwak; Jeonghan Kang; Melissa Cesaire; Kayen Tang; Robert W. Robey; William J. E. Frye; Baktiar Karim; Donna Butcher; Martin J. Lizak; Mahalia Dalmage; Brandon Foster; et al. (Acta Neuropathologica Communications)
Abstract In malignant glioma, cytotoxic drugs are often inhibited from accessing the tumor site due to the blood-tumor barrier (BTB). Ibrutinib, FDA-approved lymphoma agent, inhibits Bruton tyrosine kinase (BTK) and has previously been shown to independently impair aortic endothelial adhesion and increase rodent glioma model survival in combination with cytotoxic therapy. Yet additional research is required to understand ibrutinib’s effect on BTB function. In this study, we detail baseline BTK expression in glioma cells and its surrounding vasculature, then measure endothelial junctional expression/function changes with varied ibrutinib doses in vitro. Rat glioma cells and rodent glioma models were treated with ibrutinib alone (1–10 µM and 25 mg/kg) and in combination with doxil (10–100 µM and 3 mg/kg) to assess additive effects on viability, drug concentrations, tumor volume, endothelial junctional expression and survival. We found that ibrutinib, in a dose-dependent manner, decreased brain endothelial cell–cell adhesion over 24 h, without affecting endothelial cell viability (p < 0.005). Expression of tight junction gene and protein expression was decreased maximally 4 h after administration, along with inhibition of efflux transporter, ABCB1, activity. We demonstrated an additive effect of ibrutinib with doxil on rat glioma cells, as seen by a significant reduction in cell viability (p < 0.001) and increased CNS doxil concentration in the brain (56 ng/mL doxil alone vs. 74.6 ng/mL combination, p < 0.05). Finally, Ibrutinib, combined with doxil, prolonged median survival in rodent glioma models (27 vs. 16 days, p < 0.0001) with brain imaging showing a − 53% versus − 75% volume change with doxil alone versus combination therapy (p < 0.05). These findings indicate ibrutinib’s ability to increase brain endothelial permeability via junctional disruption and efflux inhibition, to increase BTB drug entry and prolong rodent glioma model survival. Our results motivate the need to identify other BTB modifiers, all with the intent of improving survival and reducing systemic toxicities.